The Effect of Inquiry Learning Model And Scientific Literacy Toward Students’ Critical Thinking Skills In Primary School - Anggraini, Nia Devi; Astra, I Made; Utomo, Erry (International Journal for Educational and Vocational Studies, 2020)
The aim of this study is to determine the effect of Inquiry Learning Model and Scientific Literacy toward students’ Critical Thinking Skills in Primary School. This Study was Conducted at SD Islam Al-Ikhwan Tangerang in Fifth Graders. The True Experiment Method with Two Way Anava design (treatment by level 2x2) was implemented in this study. 40 students as the sample was selected by simple random sampling. Students in experimental group were learned through Inkuiri Mandiri model. Meanwhile, in control group, students were learned through Guided Inquiry. Based on data analysis, it was obtained: (1) the student’s critical thinking skills given by Inkuiri Mandiri Model is higher than Guided Inquiry, as evidenced by Fcount (10.93) > Ftable (4.10 ); (2) there is influence of interaction between learning models and scientific literacy toward student’s critical thinking skills, this can be seen from the acquisition price of Fcount (58.926) > Ftable (4.10); (3) student’s critical thinking skills given Inkuiri mandiri Model is higher than Guided Inquiry in group of students with high scientific literacy, with the Tukey-test Qcount Test (10.986) > Qtable (4.33); and (4) student’s critical thinking skills given Inkuiri Mandiri Model is lower than Guided Inquiry in group of students who have low scientific literacy, with the Tukey-test Qcount Test (4.369) > Qtable (4.33).